APPLICATION OF THE VISSIM PROGRAM IN EVALUATION AND IMPROVING THE PERFORMANCE OF UNSIGNALED INTERSECTIONS IN PONTIANAK CITY - Mukti, Elsa Tri; Irwandi, Irwandi; Satriatama, M.Dzulfikar Andika (Fakultas Teknik Universitas Tanjungpura, 2024)
As part of transportation infrastructure, road infrastructure is essential in increasing community mobility and accessibility. When traffic volume increases or changes its characteristics, the intersection is the first thing that shows the inability to serve the increased traffic. Because intersections are critical points of the traffic system where vehicles from different directions meet, obstacles and traffic jams at intersections will affect the capacity of the road concerned, so the level of service at the intersection will decrease, including the speed, safety, and comfort of road users.This research aims to evaluate the performance of the third and fourth unsignaled intersections in Pontianak City (with a case study of the intersection of Jl. Sultan Abdurrahman-Jl. Sulawesi and the intersection of Jl. Alianyang-Jl. Putri Dara Nante-Jl. Putri Dara Hitam) and analyze alternatives to improve the performance of unsignalized intersections using Manual Kapasitas Jalan Indonesia and the VISSIM program application.The intersection performance analysis results for existing conditions at the third unsignaled intersection have a level of service value of A, and at the fourth unsignaled intersection, a level of service value of B. Based on the intersection performance analysis results, the intersection in its existing condition does not require any treatment or recommendations to improve its performance road infrastructure.